1983
DOI: 10.1111/j.1365-2362.1983.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic activity of the gastric mucosa in Ménétrièr's disease

Abstract: Biopsies of the gastric mucosa were collected from two patients with Ménétrièr's disease before, during, and after treatment with cimetidine and studied for fibrinolytic activity. The fibrinolytic activity in the homogenates or in the potassium thiocyanate soluble fractions increased markedly during the treatment. Immunological characterization of the activity indicated that its major component was an endothelium-derived type of plasminogen activator, and that the increase in activity was caused solely by an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…There is a lack of effective treatment for Ménétrier's disease. Most previous studies are case reports that report the use of antibiotics, 128 glucocorticoids, 129 and acid‐suppressants, 130 etc. A previous study has indicated that long‐acting somatostatin may be effective for the treatment of Ménétrier's disease, 131 and that hypoalbuminemia and anemia should be corrected concurrently.…”
Section: Clinical Issues and Statementsmentioning
confidence: 99%
“…There is a lack of effective treatment for Ménétrier's disease. Most previous studies are case reports that report the use of antibiotics, 128 glucocorticoids, 129 and acid‐suppressants, 130 etc. A previous study has indicated that long‐acting somatostatin may be effective for the treatment of Ménétrier's disease, 131 and that hypoalbuminemia and anemia should be corrected concurrently.…”
Section: Clinical Issues and Statementsmentioning
confidence: 99%